2012
DOI: 10.1186/1475-2875-11-324
|View full text |Cite
|
Sign up to set email alerts
|

Imported submicroscopic malaria in Madrid

Abstract: BackgroundSubmicroscopic malaria (SMM) can be defined as low-density infections of Plasmodium that are unlikely to be detected by conventional microscopy. Such submicroscopic infections only occasionally cause acute disease, but they are capable of infecting mosquitoes and contributing to transmission. This entity is frequent in endemic countries; however, little is known about imported SMM.The goals of this study were two-fold: a) to know the frequency of imported SMM, and b) to describe epidemiological, labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 24 publications
1
18
1
2
Order By: Relevance
“…Malaria was predominantly imported from Africa, as in other European countries. 4,5,[11][12][13] However, in contrast to these previous reports, 11,13 for 86.7% of patients in the present study, this was not the first attack, in comparison to, for example, only 17.8% in Slovenia, and a vast majority of patients did not take any prophylaxis. Moreover, nearly a third of the patients had started antimalarial treatment before presentation.…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…Malaria was predominantly imported from Africa, as in other European countries. 4,5,[11][12][13] However, in contrast to these previous reports, 11,13 for 86.7% of patients in the present study, this was not the first attack, in comparison to, for example, only 17.8% in Slovenia, and a vast majority of patients did not take any prophylaxis. Moreover, nearly a third of the patients had started antimalarial treatment before presentation.…”
Section: Discussioncontrasting
confidence: 83%
“…The dominant mode of importing malaria in Serbia has always been by Serbian workers hired at construction sites in malaria endemic areas, 6,7 where many stay for more than 6 months; in contrast, in Western Europe malaria mostly occurs in immigrants and tourists. 5,12 SMM was registered in 6.7% of patients, all of whom had started treatment before presentation at the hospital. A study in Madrid showed 35.5% cases of SMM, which was attributed to immunity in a large proportion of immigrants from endemic regions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the growth in international travel and migration has increased the incidence of imported malaria cases in developed countries. In Spain, submicroscopic malaria is common in sub-Saharan migrants (up to 35.5% in one series [6]) and Plasmodium ovale infection may represent up to 8% of imported malaria cases, as shown in some published series of mainly West African patients [7]. Therefore, sensitive molecular tools are needed both for malaria control programmes and for detecting with certainty malaria imported cases in patients returning from P. ovale endemic areas.…”
Section: Introductionmentioning
confidence: 99%